Rancang Bangun Prototipe Sistem Monitoring Sinkronisasi Generator ke Jaringan PLN pada PLTM Berbasis SCADA - Mada, Ridwan (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2023)
The power generator system generally consists of equipment to generate electricity, control systems, and monitoring systems. The monitoring system is usually located in a control room, which is located quite far from the generating equipment, so many use SCADA (Supervisory Control and Data Acquisition) as a solution for this. Design of a prototype monitoring system for synchronization of generators to the PLN line was carried out on a SCADA-based MHPP (Mini-Hydro Power Plant). The SCADA system presents data in the form of graphs and writings whose values are in the form of data from GPC-3 Hydro and PLC. The protocol used for communication is Modbus TCP/IP. The results of the tests that have been carried out prove that the created SCADA system is capable of monitoring RTU data from both GPC-3 Hydro and PLC in real-time while the generator is operating. The indicator is the suitability of data values between SCADA and Modbus which is connected to GPC-3 Hydro and PLC and is supported by the suitability of the time values recorded in the alarm table data and graphs.